Numerical study on the biomechanics mechanism of Type II endoleak after EVAR for Abdominal Aortic Aneurysm - Xiao Mo; Feng Zhang; Kai-Xiong Qing; Yang Xiao (PLoS ONE, 2025)
Type II endoleak, a common complication following Endovascular Aneurysm Repair (EVAR), remains a leading cause of re-intervention, yet its biomechanical mechanisms are not fully understood. This study employed an idealized model of the aneurysmal sac, Inferior Mesenteric Artery (IMA), and Lumbar Arteries (LAs) to explore endoleak mechanisms using Computational Fluid Dynamics (CFD) and Fluid-structure Interaction (FSI) simulations. The results demonstrated that pressure differences between the sac and branch arteries drive Type II endoleak, with the IMA often serving as the primary inlet. Under the influence of Type II endoleak, flow disturbances near the IMA and LAs suggest potential challenges in thrombus formation. Comparative analysis between CFD and FSI showed that CFD overestimated peak flow velocity in the IMA and underestimated sac pressure, while also displaying a temporal lag in velocity and pressure curve throughout the cardiac cycle. These findings indicate that CFD is suitable for rapid assessments where precision is less critical, whereas FSI is more appropriate for detailed mechanistic studies. This work clarifies the biomechanics of Type II endoleak and underscores the importance of selecting appropriate numerical methods in clinical and research contexts.